Multisystem inflammatory syndrome in adults in a young male following severe acute respiratory syndrome coronavirus-2 infection: a case report. Issue 1 (27th December 2021) - Kaufmann, Christoph C; Simon, Alexander; Reinhart-Mikocki, David; Publig, Sabine; Huber, Kurt; Freynhofer, Matthias K
Abstract: Background: Multisystem inflammatory syndrome in adults (MIS-A) is a rare but potentially life-threatening condition that may occur during or in the weeks following severe acute respiratory syndrome coronavirus-2 infection. To date, only case reports and small case series have described typical findings and management of patients with MIS-A. The prevalence of MIS-A is largely unknown due to the lack of data. Case summary: A 30-year-old male patient presented to the emergency department with new-onset of fever, chest discomfort, macular exanthema, abdominal pain, mild dyspnoea, and coughing. The patient reported a mildly symptomatic recent coronavirus disease-19 (COVID-19). Significantly increased markers of inflammation and a modest increase of cardiac troponin were found upon laboratory work-up at admission. Despite broad-spectrum antibiotics, the patient's clinical status deteriorated continuously. Cardiac work-up, including echocardiography, coronary angiography, and cardiac magnetic resonance imaging, was done and signs of acute myocarditis with mildly reduced left ventricular systolic function were found. The complex multi-organ symptom constellation facilitated the diagnosis of MIS-A following COVID-19 infection. Besides aspirin, intravenous, continuous hydrocortisone treatment was initiated, resulting in a prompt improvement of symptoms and clinical findings. Discussion: We report a case of successfully treated MIS-A in the context of COVID-19, which further adds to the existing literature on this rare but clinically significant condition. Our case highlights the necessity of an interdisciplinary approach to correctly diagnose this complex, multi-organ disease and enable fast and appropriate management of these high-risk patients.